NCStorage: A Prototype of Network Coding-based Distributed Storage System - Wang Lei; Yang Yuwang; Zhao Wei; Lu Wei (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Recent studies have shown that network coding can improve the performance of the distributed storage systems. However, most of these studies are theoretical which mainly focus on the bandwidth efficiency. This paper aims to provide a practical system, so NCStorage, a network-coding-based distributed storage system, is implemented. NCStorage implements network coding on the Internet, so users from all over the world can access it. Unlike traditional technologies such as erasure coding and fountain coding, re-encoding operation at storage servers is required by NCStorage. We observe that, benefiting from the re-encoding at the storage servers, the required repair bandwidth employed to repair a failed storage server is reduced, the computation overhead is balanced, and the security is enhanced. Both the encoding at the clients and the re-encoding at the storage servers are based on a deterministic algorithm. Finally, we deploy 8 storage servers in different places to evaluate the performance of the NCStorage, and the experimental results validate the analysis results.  DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3709